2020
DOI: 10.3389/fmicb.2020.539359
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites Secreted by a Plant-Growth-Promoting Pantoea agglomerans Strain Improved Rooting of Pyrus communis L. cv Dar Gazi Cuttings

Abstract: Strains belonging to Pantoea agglomerans species are known for their ability to produce metabolites that can act in synergy with auxins to induce the adventitious root (AR) formation. The latter is critically important in the agamic propagation of several woody species, including pear ( Pyrus communis L.), playing a considerable role in the commercial nursery farms including those using micropropagation techniques. When grown on a medium amended with tryptophan, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 91 publications
0
20
0
Order By: Relevance
“…The effect of this miRNA is consistent with the above miRNAs. PC-5p-194313_25 targeted to auxin-induced protein genes that are involved in the auxin signaling pathway [ 60 ]. We speculated that PC-5p-194313_25 and miRNA160 had similar functions, that is, induced by whitefly infestation and enhanced resistance via the inhibiting auxin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of this miRNA is consistent with the above miRNAs. PC-5p-194313_25 targeted to auxin-induced protein genes that are involved in the auxin signaling pathway [ 60 ]. We speculated that PC-5p-194313_25 and miRNA160 had similar functions, that is, induced by whitefly infestation and enhanced resistance via the inhibiting auxin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…was also observed [ 20 ]. Recently, Luziatelli et al [ 37 ] showed the beneficial effects of the metabolites secreted by a plant-growth-promoting Pantoea agglomerans on the Pyrus communis variety ‘Dar Gazi’ by improving its rooting. Considering the effect of the fruit phenophase on the composition of culturable microbiota, Janisiewicz et al [ 38 ] also observed a decline in the abundance of Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…The trend of gene expression without removing the transcriptional repressor is also evident in AUX signaling. βCC treatment increases the accumulation of AUX responsive proteins, namely small auxin upregulated RNA (SAUR 71) and AUX-induced proteins 15-like (homologous to the SAUR7 gene from A. thaliana) [56], without altering the expression of AUX/IAA proteins, a repressor of early auxin response genes' expression [57]. It is known that in plants, the ubiquitin system is an integral part of hormonal signal transduction.…”
Section: Discussionmentioning
confidence: 99%